Incidence of Nerve Repair Following Endoscopic Carpal Tunnel Release is Higher Compared to Open Release in New York State. Issue 2 (July 2019) - Trehan, Samir K.; Lyman, Stephen; Ge, Yile; Do, Huong T.; Daluiski, Aaron
Background: Carpal tunnel release (CTR) has traditionally been performed through an open approach, although in recent years endoscopic CTR has gained in popularity. Questions/Purposes: We sought to assess whether a difference exists between the rates of nerve repair surgery following open versus endoscopic CTR in New York State (NYS). Methods: Patients undergoing endoscopic and open CTR from 1997 to 2013 were identified from the Statewide Planning and Research Cooperative System (SPARCS) database from the NYS Department of Health using Current Procedural Terminology, 4th Revision (CPT-4) codes 29848 and 64721, respectively. The primary outcome measure was subsequent nerve repair surgery (as identified using CPT-4 codes 64831–64837, 64856, 64857, 64859, 64872, 64874, and 64876). Other variables analyzed included patient age, sex, payer, and surgery year. Results: There were 294, 616 CTRs performed in NYS from 1997 to 2013. While the incidence of open CTR remained higher than endoscopic CTR, the proportion of endoscopic CTR steadily increased, from 16% (2984/19, 089) in 2007 to 25% (5594/22, 271) in 2013. For the 134, 143 patients having a single CTR, the rate of subsequent nerve repair was significantly higher following endoscopic CTR (0.09%) compared to open CTR (0.04%). The Cox model showed that factors significantly associated with a higher risk of subsequent nerve repair surgery were endoscopic CTR and younger age. Conclusions: Endoscopic CTR has been increasingly performed in NYS and associated with a higher rate of subsequent nerve repair. This rate likely underestimates the incidence of nerve injuries because it only captures those patients who had subsequent surgery. While this catastrophic complication remains rare, further investigation is warranted, given the rise of endoscopic CTR in the setting of equivalent outcomes, but favorable reimbursement, versus open CTR.